British Museum Ethnographic Photography at the 1936 International Surrealist Exhibition. (2nd January 2020) - Walden, Lauren
Abstract : As part of the 1936 International Surrealist Exhibition held at the New Burlington Galleries in London, ethnographic photographs of non-Western objects were taken at the British Museum and interspersed amongst Surrealist artwork. Ten photographs in total were used, spanning Solomon Island Fish Coffins to Congolese Nail Fetishes. The article analyses these photographs as sculptures and in terms of their significance to the 1936 exhibition display and their wider impact upon the Surrealist movement. It reveals that Paul Nash and Hugh Sykes Davies were responsible for the selection of the non-Western objects to be photographed. At the exhibition opening André Breton gave a transformative lecture, 'Limites Non-Frontières du Surréalisme [Borderless limits of Surrealism]' which conjoined notions of cosmopolitanism and the spirit. The inclusion of the British Museum photographs was clearly intended to aesthetically mirror the content of Breton's speech. This article thus postulates that the Surrealists intended to propagate a cosmopolitan method of curation through a transcendence of taxonomic display mechanisms common to ethnographic museum environments, such as the very one the photographs were taken in. Moreover, the British Museum photographs chosen by the Surrealists all have religious and spiritual connotations. Such embodied manifestations are a particular brand of border crossing that should also be considered an element of a burgeoning discourse surrounding international Surrealism. Consequently, the oft-cited impact of Freud's Totem and Taboo (1913) upon Surrealist ethnography, which denounces the totem as a precursor to religious belief and madness, is marginalised.